Experimental investigation of thermophysical properties, tribological properties and dispersion stability of nanodiamond-based nanolubricant for air conditioning systems. (January 2023) - Aljuwayhel, Nawaf F.; Ali, Naser; Ebrahim, Shikha A.; Bahman, Ammar M.
Highlights: Thermophysical and tribological analyses of nanolubricant carried out for Air conditioning (AC) application. Nanodiamond (ND) and POE experiments examined vol.% from 0.05 to 0.5% with temperature ranges of 10 to 100°C. ND/POE nanolubricant properties data validated and correlated for density, thermal conductivity, and viscosity. 0.1 vol.% of ND/POE nanolubricant yielded the optimum minimum coefficient of friction (COF) ND/POE nanolubricant showed potential for AC compressor improvement. Abstract: Compressor oil lubricant plays a vital role in enhancing the performance of air conditioning (AC) systems. Thermophysical and tribological properties, as well as physical stability, of Polyolester (POE) oil dispersed with nanodiamond (ND) have been evaluated experimentally to determine its suitability and feasibility for utilization as a nanolubricant in AC compressors. Thermophysical properties correlations were developed for the ND/POE nanolubricant with volume percentage and temperatures ranges of 0.05 to 0.5% and 10 to 100°C, respectively. The density, thermal conductivity, and viscosity were found to increase with increasing ND particle concentration and reduced with increasing preparation temperature. The developed thermophysical properties correlations showed relatively accurate predictions with a maximum mean absolute error (MAE) of 6%. The nanolubricant at 0.1 vol.% showed the lowest coefficient of friction (COF) to improve the frictional power losses. The ND/POE nanolubricant exhibited a well-dispersed stability using both the photograph image capturing approach and ultraviolet-visible spectroscopy (UV-vis) analysis. As a result of the enhanced thermal, tribological and stability qualities, prolonged lifespan and cool operation of AC compressors are anticipated when utilizing POE oil containing up to 0.1 vol.% of ND.